Evaluation of the Analgesic Efficacy of EMLA Cream in Volunteers With Differing Skin Pigmentation Undergoing Venipuncture. Issue 2 (1st March 1999) - Riendeau, Lauren A.; Bennett, Donald; Black-Noller, Gillian; Fan, Lisha; Scavone, Joseph M.
Abstract : Background and Objectives: Lidocaine/prilocaine cream (EMLA) applied to intact skin for 60 minutes has been shown to reduce venipuncture pain. Recent studies have suggested that lidocaine/prilocaine cream is less effective on heavily pigmented skin. The objective of this study was to evaluate the topical anesthetic efficacy of lidocaine/prilocaine cream in volunteers with varying skin pigmentation types. Methods: Sixty volunteers were enrolled into each of three groups based on skin pigmentation history. Subjects were randomized to receive lidocaine/prilocaine cream onto the antecubital fossa of one arm and placebo cream on the comparable location of the other arm for either 60, 90, or 120 minutes prior to venipuncture. Assessments of perceived pain associated with each venipuncture were made by the subject using a visual analog scale. Results: Lidocaine/prilocaine cream applied for 60 minutes significantly ( P < .0001) reduced the pain of venipuncture compared to placebo regardless of the skin pigmentation type. Pain reduction did not differ significantly across skin types ( P = .7986). Additional exposure up to 120 minutes did not change the efficacy of EMLA cream. Conclusions: Lidocaine/prilocaine cream is a safe and effective topical anesthetic for reducing pain associated with venipuncture in individuals, regardless of skin pigmentation.